Including Indigenous Peoples in Geospatial Services - Moore, Thomas (Frontiers in Climate, 2022)
This article addresses the benefits and challenges to including indigenous peoples and their organizations as partners in the geospatial services provided by SERVIR-Amazonia, a USAID and NASA initiative implemented in six Amazon Basin countries: Brazil, Colombia, Ecuador, Guyana, Peru, and Surinam. It discusses who the Amazon indigenous peoples are, the significance and importance of their ancestral territories, and the benefits and importance to humanity of sharing and improving geospatial technology with them to help them defend and plan for the management and conservation of those territories. It also describes the challenges of engagement and communication with Amazon indigenous peoples, the need to work through the existing indigenous peoples' organizations (IPOs), and the importance of responding to their needs and priorities in a culturally sensitive manner with appropriate tools. Moreover, by identifying the issues involved and documenting the indigenous responses, the Program seeks to inform geospatial science and remote sensing technology with information that can help refocus their approaches to more effectively address the issues facing the indigenous peoples and their territories. The ultimate purpose is to help slow deforestation and biodiversity loss and diminish the impact of climate change, especially in the context of the COVID-19 pandemic.